Production of xylanase and β-xylosidase from autohydrolysis liquor of corncob using two fungal strains - Michelin, Michele (2012)
Agroindustrial residues are materials often rich in cellulose and hemicellulose. The use of these substrates for the microbial production of enzymes of industrial interest is mainly due to their high availability associated with their low cost. In this work, corncob (CCs) particles decomposed to soluble compounds (liquor) were incorporated in the microbial growth medium through autohydrolysis, as a strategy to increase and undervalue xylanase and b-xylosidase production by Aspergillus terricola and Aspergillus ochraceus. The CCs autohydrolysis liquor produced at 200 C for 5, 15, 30 or 50 min was used as the sole carbon source or associated with untreated CC. The best condition for enzyme synthesis was observed with CCs submitted to 30 min of autohydrolysis. The enzymatic production with untreated CCs plus CC liquor was higher than with birchwood xylan for both microorganisms. A. terricola produced 750 total U of xylanase (144 h cultivation) and 30 total U of b-xylosidase (96–168 h) with 0.75% untreated CCs and 6% CCs liquor, against 650 total U of xylanase and 2 total U of b-xylosidase in xylan; A. ochraceus produced 605 total U of xylanase and 56 total U of b-xylosidase (168 h cultivation) with 1% untreated CCs and 10% CCs liquor against 400 total U of xylanase and 38 total U of b-xylosidase in xylan. These results indicate that the treatment of agroindustrial wastes through autohydrolysis can be a viable strategy in the production of high levels of xylanolytic enzymes.